2023
DOI: 10.3390/nu15132937
|View full text |Cite
|
Sign up to set email alerts
|

Association between Gut Microbiota and Digestive System Cancers: A Bidirectional Two-Sample Mendelian Randomization Study

Abstract: Accumulating evidence indicates that gut microbiota closely correlates with the tumorigenesis of digestive system cancers (DSCs). However, whether the causality between gut microbiota and DSCs exists is unknown. Genome-wide association study (GWAS) summary statistics for gut microbiota and DSCs and the bidirectional two-sample Mendelian randomization (MR) analysis were utilized to assess the causality between gut microbiota and DSCs. Sensitivity analyses were performed to evaluate the robustness of our results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…Our study employed the MR methods to investigate a causal relationship between GM and PC, aligning with the results of previous studies. [12][13][14][15][16] They revealed various associations between different types of GM and PC due to the differences in the data sources used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study employed the MR methods to investigate a causal relationship between GM and PC, aligning with the results of previous studies. [12][13][14][15][16] They revealed various associations between different types of GM and PC due to the differences in the data sources used.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these genetic variants can potentially regulate DNA methylation (DNAm), gene expression, protein levels and the abundance of GM 10,11 . Currently, MR methods have been increasingly applied to investigate the causal relationship between GM and PC 12–16 . However, the genes potentially involved in interactions between GM and PC remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between the gut microbiota and digestive may be utilized to evaluate the impact of specific microbial communities or microbial combinations on the development and treatment of cancer. Numerous similar studies have demonstrated the significant role of MR in research on the gut microbiota and digestive tract cancer ( Ni et al, 2022 ; Li et al, 2023 ; Long et al, 2023 ; Xie et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…To explore potential causal associations, we adopted a locus-wide significance threshold at p = 1 × 10 -5 , consistent with thresholds frequently used in previous analyses ( Liu et al., 2022 ; Lopera-Maya et al., 2022 ). Additionally, in reverse MR analysis, we employed a lenient genome-wide significance threshold at p = 5 × 10 -6 to identify SNPs correlated with lymphoma ( Su et al., 2023 ; Xie et al., 2023 ). Second, to mitigate potential biases due to strong linkage disequilibrium (LD), we conducted an LD analysis with a threshold set at r² < 0.001 and a clumping distance of 10,000 kb, employing the 1000 Genomes Project European samples as a reference panel ( Purcell et al., 2007 ).…”
Section: Methodsmentioning
confidence: 99%